Interrater reliability and experiences of Assessment, Intervention, and Moving-on 3 Assessment Model in a multidisciplinary Norwegian sample - Jensen, Monica; Askeland, Ingunn Rangul; Bjørknes, Ragnhild (Frontiers in Psychology, 2022)
Background: Assessing minors with harmful sexual behavior (HSB) is a complex and sensitive task. The AIM3 Assessment Model (Leonard & Hackett, 2019) was developed to assist practitioners with information collection and HSB evaluations. Objective: In this study, we explore the interrater reliability and the practitioners’ experience with the AIM3. Participants and Setting: The multidisciplinary sample (n = 56) was recruited in Norway. The participants’ mean age is 43.2 years (SD 9.5). The sample is 79% female and 21% male. Mean years of experience is 17.6 years (SD 9.5). Methods: The participants used the Norwegian version of the AIM3 to score three case vignettes. A survey containing questions about competence and experience was filled out. We used the intraclass correlation coefficient (ICC) to estimate interrater reliability as well as descriptive statistics to show experience. Results: The estimated ICC for overall AIM3 factors is .547 (95% CI = .471, .634); for domain scores, the estimated ICC is .697 (95% CI = .548, .852). Both are in the moderate range. The majority of the participants reported that they will probably use the AIM3 in the future and that their experience with the AIM3 was highly useful with, for example, empirically informed decision-making and for intervention and safety planning. Conclusion: The moderate ICC results and the sample’s generally positive experience with the AIM3 may indicate further usefulness in a Norwegian multidisciplinary setting. We provide recommendations on how the AIM3 and similar HSB assessments can be further evaluated and developed.